Down syndrome as a genetic model to evaluate the role of oxidative stress and transsulfuration abnormalities in autism spectrum disorder: A 10‐year longitudinal cohort study. Issue 9 (4th December 2019) - Geier, David A.; Kern, Janet K.; Geier, Mark R.
Abstract: Autism spectrum disorder (ASD) is a neurodevelopmental disorder in which evidence reveals oxidative stress and transsulfuration pathway abnormalities. Down syndrome (DS) is a genetic disorder characterized by similar oxidative stress and transsulfuration pathway abnormalities. This hypothesis‐testing longitudinal cohort study determined whether transsulfuration abnormalities and oxidative stress are important susceptibility factors in ASD etiology by evaluating the rate of ASD diagnoses in DS as compared to the general population. The Independent Healthcare Research Database was analyzed for healthcare records prospectively generated in Florida Medicaid. A cohort of 101, 736 persons (born: 1990–1999) with ≥10 outpatient office visits and continuously followed for 120 months after birth was examined. There were 942 children in the DS cohort (ICD‐9 code: 758.0) and 100, 749 children in the undiagnosed cohort (no DS diagnosis). ASD diagnoses were defined as autistic disorder (ICD‐9 code: 299.00) or Asperger's disorder/pervasive developmental disorder—not otherwise specified (ICD‐9 code: 299.80). ASDs were diagnosed in 5.31% of the DS cohort and 1.34% of the undiagnosed cohort. The risk ratio of being diagnosed with an ASD in the DS cohort as compared to the undiagnosed cohort was 3.97‐fold significantly increased with a risk difference of 3.97%. Among children diagnosed with DS, less than 6% were also diagnosed with an ASD. Among children diagnosed with an ASD, less than 5% were also diagnosed with DS. Children diagnosed with DS are apparently more susceptible to ASD diagnosis relative to the general population suggesting oxidative stress and transsulfuration pathway abnormalities are important susceptibility factors in ASD.